1967
DOI: 10.1139/b67-201
|View full text |Cite
|
Sign up to set email alerts
|

INCORPORATION OF SERINE-14C AND ETHANOLAMINE-14C INTO NITROGEN-CONTAINING PHOSPHATIDES AND EFFECTS OF MEDIUM CONTAINING ETHANOLAMINE ON PHOSPHATIDE BIOSYNTHESIS IN EXCISED TOMATO ROOTS

Abstract: Work was designed to study the decarboxylation of serine and biosynthesis of ethanolamine as part of an investigation into the replacement of vitamin B6by ethanolamine in the nutrition of excised tomato roots in sterile culture. A working hypothesis to explain the replacement involves repression, by ethanolamine, of a postulated vitamin B6dependent serine decarboxylase yielding ethanolamine.Evidence is presented, from studies using uniformly labelled serine-14C, serine-1-14C, serine-3-14C, and ethanolamine-1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Willemot and Boll (37) showed that excised tomato roots metabolized "4C-serine with the production of "4C-PC and PE and poorly labeled PS. They concluded that PS was converted to PE by decarboxylation and that PC was formed from PE by successive methylation reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willemot and Boll (37) showed that excised tomato roots metabolized "4C-serine with the production of "4C-PC and PE and poorly labeled PS. They concluded that PS was converted to PE by decarboxylation and that PC was formed from PE by successive methylation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…If PE is normally made in vivo by decarboxylation of PS, we might expect that free ethanolamine would be a poor precursor of PE. In fact the opposite was true (37). It is possible that ethanolamine was introduced by an exchange reaction (35) rather than de novo synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytidylyltransferase catalyzing reaction 8 has been mentioned only very briefly as present in enzyme preparations from carrot root (20), and subsequent attempts in at least two laboratories to demonstrate this activity in extracts of higher plants were unsuccessful (25)(26)(27). Radiolabeled EA is incorporated into PtdEA (1 1,26,27,33,38,39). In certain systems, the characteristics of this incorporation are such that it was concluded that some or all of it occurred by base exchange (26,27,38), for example, reaction 2 (proceeding from right to left as written above).…”
mentioning
confidence: 99%
“…This regulation may be complex, however, since PC synthesis involves more than one pathway (10,12). For instance, in an early study of the incorporation of ['4C]serine into intact tomato roots, Willemot and Boll (18) concluded that PE was synthesized by the decarboxylation of PS, and PC by the methylation of PE. This pathway also has been found in castor bean endosperm (10), but the activity appeared to be only a fraction ofthe activity ofthe enzymes of the nucleotide pathway, in which PC is synthesized from free choline.…”
mentioning
confidence: 99%
“…Furthermore, there appears to be very little known about the serine decarboxylation reaction in any plant tissue. Although in some mammalian tissues it is clear that PS is a major precursor of PE (17), studies in plant tissues have been complicated due to apparently high turnover rates (18), low levels of PS (1 1), or an apparent lack of incorporation of radiolabeled precursors into the PS fraction (2). Marshall and Kates (9) reported the presence of a PS decarboxylase enzyme in spinach leaves, but its localization in a cytoplasmic fraction raises the possibility that the in vivo enzyme may also be involved in the decarboxylation of free serine.…”
mentioning
confidence: 99%